Indices de poder electrofílico global y local para el estudio teórico de la reactividad química: aplicación a derivados carbonilo a,ß-insaturados (2017)
In this study two new global descriptors for chemical reactivity are proposed, namely the electrophilic power and nucleophilic power. These have been developed by performing the normalization of the local electrophilic power and local nucleophilic power respectively, which were recently proposed elsewhere. In particular, the usefulness of both global and local electrophilic power was evaluated by studying the chemical reactivity of six series of a,b-unsaturated carbonyl compounds whose experimental reactivity measures toward the nucleophile glutathione are available. It was observed in the majority of the cases the global and local electrophilic powers work as better than the popular global and local electrophilicity indices, respectively.